Age-dependent changes in fat- and water-soluble vitamins—National Health and Nutrition Examination Surveys study - Tomasiuk, Ryszard; Zubrzycki, Igor Z.; Wiacek, Magdalena (Frontiers in Medicine, 2022)
Aging is an independent risk factor for the development of various diseases associated, among others, with detrimental blood levels of fat- and water-soluble vitamins. Thus, the objective of this study is to investigate age-related changes in blood levels of vitamin A, B12, C, D, and E. Subject serum vitamin levels were obtained from the combined National Health and Nutrition Examination Surveys. NHANESIII and NHANES 1999 - 2000, 2001 – 2002, 2003 – 2004, and 2005 – 2006. The raw data set was stratified into five age groups G1- G5: 20 ≤ G1 < 30, 30 ≤G2 < 40, 40 ≤ G3 < 50, 50 ≤ G4 < 60, and 60 ≤ G5 < 70 years of age. Age stratified data was cleaned using the modified Horn algorithm. The reference range for the vitamin level of a specific age group was defined as data between the first and third quartile of the subject defined by normal blood pressure and normal bone density. Age-dependent changes in serum/plasma vitamin levels were assessed using the bootstrap technique with 10,000 repeats and Bonferroni adjustment. There was a continuous increase in vitamin A, B12, D, and E levels in the blood. However, the vitamin C concentration remained virtually constant in all age groups. There was a lack of cross-correlations between lipid and water-soluble vitamin levels and cardiovascular health and bone health. The following reference levels for vitamin A, B12, C, D, and E in subjects older than 20 years of age were established: vitamin A: 1.32 - 2.8 mmol / L, vitamin B12: 257.94 - 498.33 pmol / L, vitamin C: 38.18 - 79.2mmol / L, vitamin D: 76.33 - 199.36 nmol / L and vitamin E: 3.65 - 41.12 μmol / L. Vitamin levels cannot be regarded as a parameter that defines cardiovascular and bone health at the time of measurement.